Initial experience of left bundle branch area pacing using stylet-driven pacing leads: a multicenter study. (19th May 2022) - De Pooter, J; Ozpak, E; Calle, S; Peytchev, P; Heggermont, W; Marchandise, S; Provenier, F; Francois, BART; Anne, W; Barbaud, C; Gillis, K; Vanheuverswyn, F; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left bundle branch area pacing (LBBAP) has been performed exclusively using lumen-less pacing leads (LLL) with fixed helix design. This study is the first to explore in a multicenter population the safety and feasibility of LBBAP using stylet-driven leads (SDL) with extendable helix design. Methods: This study prospectively enrolled all consecutive patients who underwent LBBAP for anti-bradycardia pacing or heart failure indications at 8 Belgian hospitals. LBBAP was attempted either using SDL or LLL delivered through dedicated delivery sheaths. Implant success, complications, procedural and pacing characteristics were recorded at implant and follow-up. Results: The study enrolled 412 patients (mean age 74 ± 38 years, 44% female). LBBAP with SDL and LLL was successful in 334/353 (94%) and 52/59 (88%) respectively (p=0.058). Implant success for LBBAP using SDL varied from 93 to 100% among centers. Mean paced QRS duration and stimulus to left ventricular activation time were comparable for SDL and LLL (126 ± 21ms versus 125 ± 22ms, p=0.861 and 74 ± 17 and 75 ± 21ms, p=0.756). SDL LBBAP resulted in low pacing thresholds (0.6 ± 0.4V at 0.4ms), which remained stable at 1, 6 and 12 months of follow-up. Lead revisions for SDL LBBAP occurred in 5(1.4%) patients: 2 dislodgements at day 1, 1 late septal perforation at week 3, 1 Twiddler's syndrome at 5 months, 1 lead fracture at 6 months. Conclusion: This multicenter study confirms the safety and feasibility of LBBAP using SDL, which is characterized by high implant success, low complication rate and low and stable pacing thresholds.